Seeded Growth Combined with Cation Exchange for the Synthesis of Anisotropic Cu2-x S/ZnS, Cu2-x S, and CuInS2 Nanorods - Xia, Chenghui (Chemistry of materials : a publication of the American Chemical Society, 2021)
© 2020 American Chemical Society.